Análise da Percepção ambiental de universitários na APA Petrópolis (RJ): estudo para uma proposta em educação ambiental para o Ensino Superior - Gonçalves, Marco Pinheiro (2011)
Nature conservation areas historically suffer with problems involving, for example, public administration and popular legitimacy, which reflects inefficiency boards and local conflicts at various levels. In this context, the Environmental Protection Area of Petrópolis (APA Petrópolis) is approached with the aim of providing an analytical framework on regional sustainability and the popular perception about the proposed APA Petrópolis, using methods in environmental perception focusing on university segments. The thesis is divided into three analytical moments: first, we present the historical, social and local political contexts of landscape, in the aim of the creation of APA Petrópolis and contradictions regarding the model, under a theoretical framework that includes local policies, management of conservation units, environmental conflicts and social participation. Second, we analyzed the environmental perception of 606 college students (through questionnaires) and seven teachers and administrators at the participating universities (through interviews) in APA Petrópolis, seeking phenomena and characteristics of subjectivity inherent in such groups. Finally, we present useful concepts to the organization of theoretical and practical alternatives to an environmental education aimed to the emancipation and reality transformation to the university segments at APA Petrópolis. The results involving the exposure of a complex historical and political context that reflects the low functioning of this model of landscape conservation. The territorial planning of the city, the establishment context for the APA, and the regional political scene are aspects that contribute to the low functionality of the APA. The questionnaires showed a superficial perception of the environmental problems of Petropolis, as well as a low recognition of the APA. Interviews, otherwise, show two phenomena: the naturalization of social issues and invisibility of environmental issues. The theoretical and methodological alternatives presented to address environmental issues to university in APA Petrópolis involve the concept of ecological literacy and training of ecological subjects, such as guidelines for an education directed to regional sustainability.